2022
DOI: 10.1111/jcmm.17196
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of PBXs and their emerging role in cancer

Abstract: Pre‐B‐cell leukaemia transcription factor (PBX) proteins are a subfamily of evolutionarily conserved, atypical homeodomain transcription factors that belong to the superfamily of three amino acid loop extension (TALE) homeodomain proteins. Members of the PBX family play crucial roles in regulating multiple pathophysiological processes, such as the development of organs, congenital cardiac defects and carcinogenesis. The dysregulation of PBXs has been shown to be closely associated with many diseases, particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 132 publications
0
26
0
Order By: Relevance
“…PBX4 belongs to the PBX family and acts as a transcriptional cofactor of HOX proteins [ 41 , 42 ], playing critical roles in multiple pathophysiological processes, such as organogenesis [ 8 , 9 ], cell differentiation [ 11 , 43 ], embryonic development [ 10 ], and spermatogenesis [ 13 ]. Recent studies have revealed that PBX4 involved cancer pathogenesis and progression [ 44 ]. However, previous research has mainly studied certain types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…PBX4 belongs to the PBX family and acts as a transcriptional cofactor of HOX proteins [ 41 , 42 ], playing critical roles in multiple pathophysiological processes, such as organogenesis [ 8 , 9 ], cell differentiation [ 11 , 43 ], embryonic development [ 10 ], and spermatogenesis [ 13 ]. Recent studies have revealed that PBX4 involved cancer pathogenesis and progression [ 44 ]. However, previous research has mainly studied certain types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…[41,42] They regulate gene expression by directly binding to the 2-8 nucleotides-seed region in 3′UTR of target mRNAs and inhibit their expression or degradation. [43,44] One single miRNA can target hundreds of mRNAs to regulate different pathways. [45] MiRNAs have been shown to be involved in pathological processes of a number of diseases, including cancers, cardiovascular diseases, autoimmune diseases, and KD.…”
Section: Mirnas With Promoting and Inhibiting Roles In Kdmentioning
confidence: 99%
“…MiRNAs are a large class of short RNA molecules with 19–24 nucleotides in length, modulating the post-transcriptional silencing of the target gene [ 87 , 88 ]. It has been reported that miRNAs can regulate the expression of many genes involved in functional interaction pathways by targeting their mRNAs [ 89 ].…”
Section: Implications Of Ncrnas In Ad Progressionmentioning
confidence: 99%